2015
DOI: 10.3233/jad-150232
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Dysfunction, Olfactory Bulb Volume and Alzheimer’s Disease: Is There a Correlation? A Pilot Study1

Abstract: The reduction of OBV does not seem to represent an index of neuronal damage in the earliest stages of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In relation to categorical stratification, the identification of odors was measured 40 times, 15 - 52 discrimination 21 times 16 , 21 , 22 , 26 , 29 , 34 , 35 , 37 , 38 , 46 , 53 - 61 and recognition only 6 times, 17 , 18 , 40 , 57 , 62 , 63 representing samples of 3328, 1062 and 244 evaluated individuals, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to categorical stratification, the identification of odors was measured 40 times, 15 - 52 discrimination 21 times 16 , 21 , 22 , 26 , 29 , 34 , 35 , 37 , 38 , 46 , 53 - 61 and recognition only 6 times, 17 , 18 , 40 , 57 , 62 , 63 representing samples of 3328, 1062 and 244 evaluated individuals, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis in relation to smoking could not be performed due to insufficient information: only 9 studies 19 , 22 , 26 , 27 , 36 , 42 , 44 , 46 , 47 employed this item as an exclusion criterion and only 5 articles 20 , 21 , 25 , 29 , 34 reported the number of smokers present in the sample. The same situation occurred for onset and duration of symptoms of AD, with insufficient data available.…”
Section: Resultsmentioning
confidence: 99%
“…Several neuroimaging studies have found associations between OI dysfunction and structural abnormities in brain regions that contribute to olfactory processing, such as the olfactory cortex (OC). The OC is the center of olfactory processing and functional and structural anomalies are strongly implicated in OI dysfunction (Thomann et al, 2009b; Servello et al, 2015; Vasavada et al, 2017). Hippocampal atrophy is a well-known pathological feature of AD and MCI (Prestia et al, 2010), and so may also contribute to OI dysfunction in AD and MCI.…”
Section: Introductionmentioning
confidence: 99%
“…In human autopsy studies, amyloid and tau, as well as other pathologies such as progranulin and TDP-43 deposition, are found in the olfactory bulb and throughout the olfactory network (including temporal piriform cortex) in patients with AD and other neurodegenerative diseases, and levels of amyloid and tau deposition are associated with the level of olfactory deficits [23] , [24] , [25] , [26] , [27] , [28] , [29] , [34] . The associations of UPSIT performance with neurodegeneration and brain function, measured using magnetic resonance imaging (MRI) or [ 15 O]H 2 O PET, have also been investigated [4] , [14] , [31] , [35] , [36] , [37] , [38] , [39] , [40] , [41] . In vivo imaging studies have shown weak associations between amyloid and olfactory impairments [30] , [31] , [32] .…”
Section: Introductionmentioning
confidence: 99%